Measurement of suppression of large-radius jets and its dependence on substructure in Pb+Pb collisions at √𝑠𝑁⁢𝑁=5.02 TeV with the ATLAS Detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; et al. (Physical review letters, 2023)
This letter presents a measurement of the nuclear modification factor of large-radius jets in √𝑠𝑁⁢𝑁 =5.02  TeV Pb+Pb collisions by the ATLAS experiment. The measurement is performed using 1.72  nb−1 and 257  pb−1 of Pb+Pb and 𝑝⁢𝑝 data, respectively. The large-radius jets are reconstructed with the anti-𝑘𝑡 algorithm using a radius parameter of 𝑅 =1.0, by reclustering anti-𝑘𝑡 𝑅 =0.2 jets, and are measured over the transverse momentum (𝑝𝑇) kinematic range of 158<𝑝𝑇<1000  GeV and absolute pseudorapidity |𝑦| <2.0. The large-radius jet constituents are further reclustered using the 𝑘𝑡 algorithm in order to obtain the splitting parameters, √𝑑12 and Δ⁢𝑅12, which characterize the transverse momentum scale and angular separation for the hardest splitting in the jet, respectively. The nuclear modification factor, 𝑅𝐴⁢𝐴, obtained by comparing the Pb+Pb jet yields to those in 𝑝⁢𝑝 collisions, is measured as a function of jet transverse momentum (𝑝𝑇) and √𝑑12 or Δ⁢𝑅12. A significant difference in the quenching of large-radius jets having single subjet and those with more complex substructure is observed. Systematic comparison of jet suppression in terms of 𝑅𝐴⁢𝐴 for different jet definitions is also provided. Presented results support the hypothesis that jets with hard internal splittings lose more energy through quenching and provide a new perspective for understanding the role of jet structure in jet suppression.